Genetic analysis of the effect of sodium azide (chemical mutagen) induction on three Cameroonian Okra (Abelmoschus esculentus (L.) Moench) varieties’ growth characteristics, yield, and enzymatic activities - Njock, Raphaël Siméon; Likeng-Li-Ngue, Benoit Constant; Nkoulou, Luther Fort Mbo; Ndjaga, Jude Manga; Ngalle, Hermine Bille; Bell, Joseph Martin (Journal of Scientific Agriculture, 2025)
Abelmoschus esculentus is a plant with nutritional and medical properties, therefore environmental circumstances are progressively affecting production. The aim of this study was to contribute to the development of genetic variability in three okra varieties exposed to sodium azide (SA). In this study, sodium azide (0 g/L, 2 g/L, 4 g/L, and 6 g/L for 6 hours) was administrated to three okra seeds (Locale 1, Yellen, and Hire) in the field. Descriptors like seed germination rate, plant height (PH), stem diameter (SD), number of leaves per plant (NLP), foliar area (FA), number of fruits per plant (NFP), and number of seeds per fruit (NSF) were used to analyze genetic variability, broad-sense heritability (H²), and genetic advance (GA) in three okra varieties. The results showed that the Yellen variety had the highest percentage of seed germination (100% in M1 and M2 for control (T0), to 41.67% (M1) and 44.44% (M2) for T3) as well as POX (71.01% for M1 and 128.84% for M2) and CAT (198.03% for M1 and 125.80% for M2) activities. It also had the highest NFP in the T0, with values between 1.25±2.29 in M1, and 14.42±2.11 in M2 (p˂0.05). In terms of productivity, the Hire variety outperformed with elevated FW1F (16.21 g for M1, and 25.87 g for M2) and DW1F (15.44 g for M1, and 23.10 g for M2) values. However, the explained variance of the induction of sodium azide was R²=0.101 for growth parameters, R²=0.377 for productivity parameters, and R²=-0.218 for enzymatic activities. Following M2 generations, characters FA and NFP displayed high genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), broad-sense heritability, and genetic advance as percent of mean (GAM) levels. Therefore, chemical mutagenesis offers a straightforward method for introducing mutations within plants through hybridization, which can increase favorable crop improvement programs.